The political anatomy of domination - Hibou, Beatrice (Paris Palgrave Macmillan, 2011)
Rereading Marx, Weber, Gramsci and, more recently, Foucault, Bǎtrice Hibou tackles one of the core questions of political and social theory: state domination. Combining comparative analyses of everyday life and economics, she highlights the arrangements, understandings and practices that make domination conceivable, bearable, even acceptable or reassuring. To carry out this demonstration, Hibou examines authoritarian situations―especially comparing the paradigmatic European cases of fascism, Nazism and Soviet socialism and those of contemporary China or North and Sub-Saharan Africa.
Includes index
Keywords: Politics